2011
DOI: 10.1586/eem.11.25
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor action: defining a role in breast cancer

Abstract: The ovarian steroid hormones, estradiol and progesterone, and their nuclear receptors (estrogen receptor [ER] and progesterone receptor [PR]), are involved in breast cancer development. As ER-positive/PR-positive tumors progress, they are likely to become steroid hormone-resistant/independent, yet often retain expression of their steroid receptors. Notably, up to 40% of women with steroid receptor-positive tumors exhibit de novo resistance or eventually fail on estrogen- or ERα-blocking therapies (acquired res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 93 publications
(135 reference statements)
2
98
0
2
Order By: Relevance
“…This might have contributed to the lower pCR rate in PR positive patients in our study, as 89 % of our patients received taxane-based chemotherapy. Other studies have demonstrated an upregulation of the anti-apoptotic gene BCL-XL in breast cancer cells as a consequence of PR expression [27]. The main cytotoxic mechanism of taxanes is apoptosis, and this might contribute to the relative resistance of PR positive carcinomas to taxanes.…”
Section: Discussionmentioning
confidence: 97%
“…This might have contributed to the lower pCR rate in PR positive patients in our study, as 89 % of our patients received taxane-based chemotherapy. Other studies have demonstrated an upregulation of the anti-apoptotic gene BCL-XL in breast cancer cells as a consequence of PR expression [27]. The main cytotoxic mechanism of taxanes is apoptosis, and this might contribute to the relative resistance of PR positive carcinomas to taxanes.…”
Section: Discussionmentioning
confidence: 97%
“…The highest proliferative activity occurs in the luteal phase of the menstrual cycle (when the endogenous progesterone concentration is high). (29) Daniel et al (8) state that progestin added to HRT significantly increases the incidence of breast tumors and the breast tumor stage in females who are in menopause. Therefore progesterone is no longer considered a completely (30) more than 70% of breast cancers express the estrogen receptor alpha (ERα) and respond to antiestrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) The results of epidemiological and clinical research showed strong evidence on the role of estrogen/ progesterone in the formation of breast cancer, but the exact mechanism of tumor formation is not yet completely understood. (7,8) According to Urban et al, (9) there was an increased risk of breast cancer associated with the use of HC, i.e. pills and/or injections (OR=1.66; 95% CI: 1.28 -2.16; p<0.001), pills only (OR=1.57; 95% CI: 1.03-2.40; p=0.04), injections only (OR=1.83; 95% CI: 1.31-2.55; p<0.001).…”
Section: Introductionmentioning
confidence: 99%
“…If dogs and other canids are functional PR-B knockouts but they can develop normal mammary glands, this may be true also for other species. No studies are presented to our knowledge with respect to the role of PR-isoforms in human mammary development, but in humans the overexpression of PR-A, and/or the loss of PR-B, is associated with a more malignant mammary phenotype [45,46]. The question is whether this explains the high incidence of mammary tumors in dogs having only a functional PR-A, and if PR-A alone is sufficient in humans to stimulate mammary development and carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%